The Impact of Teachers' Instructional Beliefs on Their Teaching Implications for Research and Practice - Bauch, Patricia A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This study investigated the instructional beliefs of 182 elementary classroom teachers to determine the degree to which teachers' assumptions about instructional practices influence their teaching behavior and the classroom perceptions of their students. It used data collected from a national research project, Goodlad's "A Study of Schooling." Discriminant and content analyses were conducted on data representing various sources and perspectives on the classroom curriculum of each teacher. While it was found that teachers' instructional beliefs were generally consistent with their teaching behaviors, only one of the four teacher belief types investigated exhibited a wide range of teaching skill reinforced by the expressed intention to accomplish a broad set of instructional outcomes. Their classrooms also tended to score higher than those of the other three teacher types on student perceptions of a positive classroom environment. Implications for both research and practice are discussed. (Author)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 23-27, 1984).
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beliefs; Classroom Environment; Data Analysis; Educational Principles; Elementary Education; Teacher Attitudes; Teacher Behavior; Teacher Characteristics; Teacher Effectiveness; Teacher Influence; Teacher Response; Teacher Role; Values; Study of Schooling (A); Reports, Research